The Rare Cancer Network: ongoing studies and future strategy - Ozsahin, Mahmut; Mirimanoff, Rene-Olivier; Thariat, Juliette; Sun, Xu Shan; Atalar, Banu; Lassen-Ramshad, Yasmin; Ugurluer, Gamze; Krishnan, Sunil; Hallemeier, Christopher; Van Houtte, Paul; Krengli, Marco; Zhang, Lan Jun; et al. (SAGE PUBLICATIONS LTD, 2014)
The Rare Cancer Network (RCN) was formed in the early 1990's to create a global network that could pool knowledge and resources in the studies of rare malignancies whose infrequency prevented both their study with prospective clinical trials. To date, the RCN has initiated 74 studies resulting in 46 peer reviewed publications. The First International Symposium of the Rare Cancer Network took place in Nice in March of 2014. Status updates and proposals for new studies were heard for fifteen topics. Ongoing studies continue for cardiac sarcomas, thyroid cancers, glomus tumors, and adult medulloblastomas. New proposals were presented at the symposium for primary hepatic lymphoma, solitary fibrous tumors, Rosai-Dorfman disease, tumors of the ampulla of Vater, salivary gland tumors, anorectal melanoma, midline nuclear protein in testes carcinoma, pulmonary lymphoepithelioma-like carcinoma, adenoid cystic carcinoma of the trachea, osteosarcomas of the mandible, and extra-cranial hemangiopericytoma. This manuscript presents the abstracts of those proposals and updates on ongoing studies, as well a brief summary of the vision and future of the RCN.
Keywords: rare; diseases; cancer; carcinoma; Rare Cancer Network